2014
DOI: 10.1098/rstb.2013.0347
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive gains through repeated gene loss: parallel evolution of cyanogenesis polymorphisms in the genusTrifolium(Fabaceae)

Abstract: Variation in cyanogenesis (hydrogen cyanide release following tissue damage) was first noted in populations of white clover more than a century ago, and subsequent decades of research have established this system as a classic example of an adaptive chemical defence polymorphism. Here, we document polymorphisms for cyanogenic components in several relatives of white clover, and we determine the molecular basis of this trans-specific adaptive variation. One hundred and thirty-nine plants, representing 13 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…Gene presence/absence data for CYP79D15 were obtained from previous publications (Olsen et al ., , ). PCR amplification of clover candidate genes for the second and third steps in CNglc synthesis (referred to below as C YP736A187 and UGT85K17 , respectively) initially used Lotus japonicus primer sequences (Takos et al ., ), after which clover‐specific primers were designed and used in all analyses (Table S3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene presence/absence data for CYP79D15 were obtained from previous publications (Olsen et al ., , ). PCR amplification of clover candidate genes for the second and third steps in CNglc synthesis (referred to below as C YP736A187 and UGT85K17 , respectively) initially used Lotus japonicus primer sequences (Takos et al ., ), after which clover‐specific primers were designed and used in all analyses (Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…For the Ac/ac (CNglc) polymorphism, we observed that the recessive ac allele corresponds to a deletion of CYP79D15 , the cytochrome P450 that catalyzes the first dedicated step in the three‐step CNglc biosynthesis pathway (Olsen et al ., ). Molecular evolutionary studies further indicated that both the Ac/ac and Li/li adaptive polymorphisms have evolved through selection favoring recurrently evolving gene deletions, and that this has occurred both in white clover (Olsen et al ., ; Kooyers & Olsen, ) and in several related Trifolium species (Olsen et al ., ). However, all molecular studies of the Ac/ac (CNglc) polymorphism to date have focused solely on CYP79D15 , as the genes encoding the second and third metabolic steps have remained unidentified in clover.…”
Section: Introductionmentioning
confidence: 97%
“…Our study suggests that wild plant populations are rapidly adapting to the unique environmental conditions associated with urbanization, and highlights white clover as a model system for the study of adaptation in urban ecosystems. Clines in cyanogenesis arise from spatial sorting of standing genetic variation at cyanogenesis loci [18], which probably explains the rapid evolution of these clines [42]. White clover is the most abundant source of nectar for pollinators in many temperate ecosystems [43].…”
Section: Discussionmentioning
confidence: 99%
“…linamarin and lotaustralin), and Li, which encodes the hydrolyzing enzyme, linamarase. Plants must have dominant alleles at both loci to produce HCN [18]. The two components (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution to this issue by Olsen et al [112] on cyanogenesis (the production of hydrogen cyanide in damaged plant tissue, which in turn functions to reduce the activity of herbivores) in the genus Trifolium (clovers) is illustrative rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Introductionmentioning
confidence: 99%